PENGARUH PENDAPATAN ASLI DAERAH DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN SERDANG - Ardhansyah Putra Harahap (Universitas Dharmawangsa, 2018)
This study aims to determine: (1) the influence of local revenue (PAD) on economic growth in SerdangBedagai regency, (2) the effect of capital expenditure on economic growth in Serdang Bedagai Regencyof North Sumatra Province. This research is a causal design research that is useful to analyze therelationship between one variable with other variables. Variables in this research consists ofindependent variables namely PAD and capital expenditure while the dependent variable is EconomicGrowth. The population in this study consists of 1 District and the study sample consists of 17 districts.Sampling technique in this research by purposive sampling. The study was conducted in SerdangBedagai District. The implementation of the research was conducted for 6 months